The effect of athletics and football training characteristics on some respiratory parameters in female athletes - Kahraman, Muhammed Zahit; Okut, Sedat; Sarı, Cengizhan; Bilici, Ömer Faruk; Bilici, Muhammed Fatih (My University, 2023)
The aim of this research is to examine the effect of training characteristics specific to athletics and football branches on some respiratory parameters in female athletes. 15 female long-distance runners (age: 18.86 ± 1.18 years), 15 female football players (age: 20.40 ± 1.24 years), and 15 female sedentary (age: 20.26 ± 2.05 years) participated voluntarily in the study. The respiratory function values of the participants were determined using a spirometer device. A one-way ANOVA test was applied to compare the mean of respiratory parameters between groups. Tukey post-hoc test was used to determine which group caused the difference in cases where there was a significant difference. In the research findings, the forced vital capacity (FVC), the volume of air exhaled in the first second of forced expiration (FEV1), the volume of air exited in the first second/forced vital capacity (FEV1/FVC), peak expiratory flow rate (PEF), forced expiratory flow between 25% and 75% of vital capacity (FEF25-75%), vital capacity (VC) and maximal voluntary ventilation (MVV) values of the long-distance runners were statistically significantly higher than the sedentary (p<0.05). It was determined that the FEV1, PEF, and FEF25-75% values of the long-distance runners were significantly higher than the football players (p<0.05), and there was no significant difference between other parameters (p>0.05). It was found that the football players' PEF and MVV values were significantly higher than the sedentary (p<0.05). As a result, it was determined that the respiratory functions of female long-distance runners were better compared to football players and sedentary females. Training characteristics of long-distance runners can be applied for better development of respiratory functions.
Keywords: Training; football; Athletics; respiratory functions; long-distance runners